2013
DOI: 10.1111/petr.12061
|View full text |Cite|
|
Sign up to set email alerts
|

Increased risk of gastrointestinal acute GVHD following the addition of melphalan to busulfan/cyclophosphamide conditioning

Abstract: Risk factors associated with the development of aGVHD in the gastrointestinal tract have not been studied in depth. We retrospectively assessed 25 pediatric patients with MDS and JMML and compared the treatment outcome of two different conditioning regimens. Seventeen children (68%) underwent conditioning with busulfan (Bu), cyclophosphamide (Cy), and melphalan (Mel) and eight children (32%) with Bu and Cy. Gastrointestinal aGVHD stages II-IV (day 0-100) were observed in 47% (eight of 17) of the patients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Furthermore, the acute GVHD rates were higher in the 1575-cGy group, suggesting that the relapse protection may not be from a direct anti-leukemic effect, but rather from induction of increased alloreactivity. Similar concerns were recently raised regarding the benefit of melphalan in the conditioning regimen of children with JMML and MDS, where patients who non-randomly received BU–CY alone had less aGVHD of the gastrointestinal tract than those who received BU–CY–MEL, with at least equivalent OS rates (60). …”
Section: Conditioning Regimen and The Transplant Processmentioning
confidence: 71%
“…Furthermore, the acute GVHD rates were higher in the 1575-cGy group, suggesting that the relapse protection may not be from a direct anti-leukemic effect, but rather from induction of increased alloreactivity. Similar concerns were recently raised regarding the benefit of melphalan in the conditioning regimen of children with JMML and MDS, where patients who non-randomly received BU–CY alone had less aGVHD of the gastrointestinal tract than those who received BU–CY–MEL, with at least equivalent OS rates (60). …”
Section: Conditioning Regimen and The Transplant Processmentioning
confidence: 71%
“…We conducted a subgroup analysis by orally or by an IV infusion route during the conditioning regimen before HSCT, thereby demonstrating that the incidence of graft failure significantly decreased at a cut-off level of > 900 μM × min in subgroup of administration by an IV infusion route. As we know, oral Bu presents a wide inter-and intrapatient variability of plasma exposures, especially in young children, which results in poor clinical outcomes [35]. That might explain why the oral Bu subgroup did not show significance at the 900 μM × min cut-off level.…”
Section: Discussionmentioning
confidence: 95%
“…Our sensitivity analysis further validated the cut-off value CI Confidence interval 900 μM × min for efficacy. In addition, numerous studies [19,35] have found that the first-dose Bu AUC was significantly lower than the subsequent daily ones and AUC remained unchanged during the following days. However, we cannot identify the relationship between AUC at the first dose and efficacy as there is insufficient data from studies to support this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, survival rates are not improving over time, as evidenced by the poor EFS seen in patients undergoing umbilical cord blood transplant between 1995 and 2010. 79 Small, nonrandomized studies suggest that elimination of Mel 101 and/or substitution of Cy with fludarabine 102 may decrease acute graft-versus-host disease and acute toxicities without affecting overall survival. The current COG ASCT1221 trial is testing the hypothesis that the main mechanism of disease elimination in patients with JMML is primarily a result of the alloreactive graft-versus-leukemia effect, and therefore that less toxic regimens could potentially be used to establish successful engraftment with similar rates of survival.…”
Section: Approaches To Hsctmentioning
confidence: 99%